Human resource management practices and sales force retention of FMCG organization in Bangladesh: a quantitative analysis on Square Toiletries Ltd. - Meem, Irin Sultana (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.